Aging and Universal Health Coverage: Implications for the Asia Pacific Region - Sarah L. Barber; Megumi Rosenberg (Taylor & Francis Group, 2017)
Global population aging is the result of successes in public health, enabling longer life expectancy in many countries. The Asia Pacific region is aging more rapidly than many other parts of the world. The implications will be profound for every sector of society, requiring policy makers to reframe their thinking about the design of health and social systems to enable older populations to thrive. With increasing demand for more and different kinds of services, an imperative is shifting resources toward primary care for the prevention and comprehensive care of people with chronic conditions, and establishing linkages with community support. Major innovations are underway that accelerate progress in attaining universal health coverage for older populations. The renewed commitments under the Sustainable Development Goals to achieve universal health coverage offer a unique opportunity to invest in the foundations of the health system of the future.